Natural occurrence of fumonisins and characteristics of pamonhas sweet type from Southern Brazil. Issue 3 (3rd July 2017) - Silva, Bruna A.; Rosa, Rafaela; Silva, Juliana R.; Savi, Geovana D.; Scussel, Vildes M.
ABSTRACT: Fresh and frozen pamonhas, a native Brazilian food made with sweet corn ( Zea mays L.), similar to the Mexican tamal, which has been incorporated into the country's diet, were investigated for fumonisins (FBs: FB1 and FB2 ) contamination and product characteristics. The laboratory conditions of the applied fumonisins method with liquid chromatography and fluorescence detection were validated. Five out of the total samples showed FBs contamination above the national maximum level of 1000–1500 µg/kg. Despite this, in 59.6% (31) of the samples FB1 and in 23.1% (12) FB2 could be detected. The pamonhas characteristics did not show uniformity among the brands surveyed. The moisture content of 59.4% and water activity of 0.97 for both (fresh and frozen) samples showed to be suitable conditions for fungal growth. One sample had a quite high pH. It is essential to establish guidance criteria for pamonha production by the regulatory agencies.